Names of colours in Russian fashion magazines (prototypisation and structural analysis) - Romanik, Anna (Papers in Linguistics, 2019)
This paper provides a structural and semantic analysis of colour names excerpted from glossy Russian fashion magazines. Special attention was paid to illustrate the prototypes of researched names. It was found that the names of colours and shades were derived from the names of flowers, fruits, minerals, dishes and food, phenomenon of nature etc. The analysis also includes a description of the structural properties of selected constructions. One-word names of colour are expressed by nouns and adjectives. The most productive models of colour name are compound words and expressions consisting of multiple elements. Their popularity stems from the fact that such constructions have a wider ability to add detail to concepts. It was also observed that names of colours used in fashion discourse are very important elements of an advertised commodity and should attract the attention of readers.